Atmospheric dispersion modelling of a natural CO2 degassing pool from Campo de Calatrava (northeast Spain) natural analogue. Implications for carbon storage risk assessment. (April 2016) - Gasparini, A.; Sainz-García, A.; Grandia, F.; Bruno, J.
Highlights: Study of a natural analogue for risk assessment. Experimental and numerical modelling approach was applied. Technique validation for measuring the flux of a CO2 single point emission site. We did an experimental and numerical modelling approach to prove methods and results. Abstract: Carbon dioxide is an essential gas for life on earth although it can be lethal to living beings at high concentrations in the atmosphere. Episodic release of CO2 from underground can occur either from natural processes (i.e., mantle degassing, thermal decarbonation) or industrial (geological storage of CO2, CCS). CO2 is a colourless and odourless gas denser than air, and once released in the atmosphere from point sources, its dynamics is initially governed by buoyancy and a gas cloud can accumulate above the ground (gravitational phase) leading to the formation of the so-called "CO2 lakes". With time, CO2 distribution is then governed by wind and atmospheric turbulence (passive dispersion phase). Natural analogues provide evidences of the impact of CO2 leakage on vegetal cover, wild life and human beings. In this work, the dynamics of CO2 in the atmosphere after ground emission is assessed to quantify their potential risk. Two approaches have been followed: (1) direct measurement of air concentration in a natural emission site, where formation of a "CO2 lake" is common and (2) numerical atmospheric modelling with the TWODEE code. The studied site is located in the Campo de Calatrava region in central Spain, which is known for a widespread degassing of mantle-derived CO2 . This site, called Cañada Real, has a degassing rate between 1 and 3 tonnes of CO2 per day. When atmospheric conditions are quite stable, i.e., negligible wind speed, the formation of a blanket of CO2 -enriched air is visible at naked eye reaching up to 50 cm high. The CO2 concentration measured in air is typically higher than 10, 000 ppm in most monitoring stations. The measured data are consistent with the numerical models that predict maximum concentration between 40, 000 and 70, 000 ppm CO2 in air, which is by far higher than the 30, 000 ppm threshold from which hazardous effects on human beings are observed. Conclusions from this work, however, indicate that the risk for humans even at large emission rates is low due to the CO2 dispersion effect into the atmosphere, and only under very particular conditions lethal effects are predicted.